Ralph J. Perk, the “New ethnicity”, and the making of urban ethnic republicans - Merton, Joe (Cambridge University Press, 2017)
Historians seeking to explain the late twentieth century rightward shift of urban ethnic whites have tended to ignore the shifting meaning and content of white ethnic identity in this transition, and the utility of these changes to conservative political discourse. This article, focusing on the ethnic strategies of the Republican mayor of Cleveland, Ralph Perk, seeks to illustrate the importance of the “New Ethnicity” of the 1970s, and its reconceptualization of white ethnicity as a series of “values”, in the making of urban ethnic Republicans. In doing so it reorients our understanding of Perk – the “Ethnic Mayor” – and places ethnicity at the heart of the conservative insurgency reshaping urban and national politics during this period.